A hermite radial basis functions control volume numerical method to simulate transport problems - Orsini, Paolo (2009)
This thesis presents a Control Volume (CV) method for transient transport problems where the cell surface fluxes are reconstructed using local interpolation functions that besides interpolating the nodal values of the field variable, also satisfies the governing equation at some auxiliary points in the interpolation stencils. The interpolation function relies on a Hermitian Radial Basis Function (HRBF) mesh less collocation approach to find the solution of auxiliary local boundary/initial value problems, which are solved using the same time integration scheme adopted to update the global control volume solution. By the use of interpolation functions that approximate the governing equation, a form of analytical upwinding scheme is achieved without the need of using predefined interpolation stencils according to the magnitude and direction of the local advective velocity. In this way, the interpolation formula retains the desired information about the advective velocity field, allowing the use of centrally defined stencils even in the case of advective dominant problems. This new CV approach, which is referred to as the CV-HRBF method, is applied to a series of transport problems characterised by high Peclet number.